PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN METODE BERMAIN LOMPAT BAN DAN KARDUS - M. Masrukhan (Indonesian Journal of Education Teaching and Learning (IJETL), 2024)
Masrukhan (NIM: 212223212). Tuck Style Long Jump Learning Using the Tire and Cardboard Jumping Playing Method for Class VI Students of Semedo State Elementary School, Kedungbanteng District, Tegal Regency, Academic Year 2023/2024. Courses of Physical Education, Health and Recreation, 2024, 173 pages. The aim of this research is an effort to achieve competency for class VI students of Semedo State Elementary School, Kedungbanteng District, Tegal Regency, Academic Year 2023/2024 in the ability to tuck style long jump using the tire and cardboard jumping playing method. In accordance with the research objectives, this research is in the form of quantitative research and refers to Classroom Action Research (CAR), which consists of 2 cycles. The population in this study was class VI students of Semedo State Elementary School, Kedungbanteng District, Tegal Regency, Academic Year 2023/2024, totaling 22 students consisting of 12 male students and 10 female students. The data sources in this research come from teachers and students. The data collection technique is observation and assessment of tuck style long jump learning results. Data analysis was carried out by observing the tuck style long jump movement, then the results were compared with the minimum tuck style long jump learning results that must be achieved. The research results show that using the tire and cardboard jumping playing method can improve students' tuck style long jump learning results from pre-cycle to cycle I and from cycle I to cycle II. The learning process in the pre-cycle does not yet use the tire and cardboard jumping playing method to help students learn the tuck style long jump movement so that students' tuck style long jump learning results are still low and students' tuck style long jump learning results are less than optimal. From the results of the analysis, a significant increase was obtained from pre-cycle to cycle I and from cycle I to cycle II. In the pre-cycle, students who completed reached 40.91%. In cycle I, students who completed reached 68.18%. Meanwhile in cycle II it reached 81.82%. The conclusion of this research is that the use of tire and cardboard jumping playing method can improve the tuck style long jump learning results of class VI students of Semedo State Elementary School, Kedungbanteng District, Tegal Regency, Academic Year 2023/2024.